2015
DOI: 10.1093/jxb/erv364
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and iron deficiencies induce a metabolic reprogramming and affect the exudation traits of the woody plantFragaria×ananassa

Abstract: Strawberries are a very popular fruit among berries, for both their commercial and economic importance, but especially for their beneficial effects for human health. However, their bioactive compound content is strictly related to the nutritional status of the plant and might be affected if nutritional disorders (e.g. Fe or P shortage) occur. To overcome nutrient shortages, plants evolved different mechanisms, which often involve the release of root exudates. The biochemical and molecular mechanisms underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 91 publications
6
49
0
1
Order By: Relevance
“…2). These results correlate with recent metabolomic data, revealing that Pro accumulation is one of the consequences of phosphorus deficiency in several plant species (Pant et al, 2015b;Valentinuzzi et al, 2015). Pro accumulation in phosphatestarved plants is driven by enhanced expression of P5CS1, encoding the key enzyme in the Pro biosynthetic pathway.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…2). These results correlate with recent metabolomic data, revealing that Pro accumulation is one of the consequences of phosphorus deficiency in several plant species (Pant et al, 2015b;Valentinuzzi et al, 2015). Pro accumulation in phosphatestarved plants is driven by enhanced expression of P5CS1, encoding the key enzyme in the Pro biosynthetic pathway.…”
Section: Discussionsupporting
confidence: 88%
“…Comprehensive metabolic profiling of phosphate-starved Arabidopsis plants revealed massive changes in primary and secondary metabolites, such as organic acids, sugars, glucosinolates, flavonoids, and amino acids, including Pro (Morcuende et al, 2007;Pant et al, 2015b;Valentinuzzi et al, 2015).…”
mentioning
confidence: 99%
“…(Arango et al, 2003), Vitis vinifera (Pii et al, 2014), and Fragaria vesca (Valentinuzzi et al, 2015). The amino acid sequences were obtained from public databases 1, 2 , 3 (The Arabidopsis Information Resource (TAIR), MSU) and the relative accession numbers were reported in Supplementary Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the increased accumulation of organic acids, particularly citric acid, in roots facilitating Fe mobilization (Rellán-Álvarez et al, 2011;Valentinuzzi et al, 2015), metabolite profiles reported in Figure 8 and Table II showed that Fe deficiency induced an accumulation of Glc and Fru. A drop of pyruvic acid in plants exposed to sulfate deficiency indicates a slowdown of the glycolytic pathway, especially prevalent under combined Fe and S starvation, where additionally Glc-6-P levels were reduced (Fig.…”
Section: Is There a Differential Metabolic Response To Fe Deficiency mentioning
confidence: 99%